Expansion of the sand fly fauna of Slovenia - Ivović, Vladimir (Acta entomologica slovenica (Ljubljana), 2025)
Phlebotomine sand flies (Diptera: Psychodidae) are important vectors of human and animal pathogens, including Leishmania spp. parasites and phleboviruses. In this study, we report the first record of Phlebotomus perfiliewi Parrot, 1930 in Slovenia, based on material obtained during systematic vector surveillance conducted in 2023 and 2024 in the Primorska region. Sampling was performed monthly from May to October on a rural tourist farm Medljan in Cetore, using CDC light traps. Morphological identification of specimens was based on key characters of cibarial armature, spermathecae, and male genitalia. In 2023, three specimens of P. perfiliewi (2>, 1+) were collected. In 2024, nine ad- ditional individuals (8>, 1+) were recorded, suggesting the presence of an emerging local population. This species, previously widespread in Italy and parts of the central and southern Balkans, had not been recorded in northern Dalmatia, Istria, or Slovenia until now. Given the proximity of the sampling site to northeastern Italy, the population likely represents a recent expansion across the border. As P. perfiliewi is a proven vector of L. infantum, its presence raises concerns about the possible establishment of autochthonous transmission cycles in Slovenia. Further molecular studies are needed to confirm the origin and genetic relatedness of the population. These findings highlight the importance of continuous entomological monitoring in response to environmental change and expanding vector distributions in Europe.
Keywords: first record; peščene muhe; Phlebotomus perfiliewi; prva najdba; sand flies; Slovenia; Slovenija; spremljanje prenašalcev; vector surveillance